Teacher Welfare and Its Impact on Teaching Quality and Educational Outcomes: Evidence from Purworejo Regency, Indonesia - Rifian Budiansyah; Much Nuril Huda (LPTK UIN Syekh Wasil Kediri, 2025)
This study aims to analyze the effect of teacher welfare on teaching quality and educational outcomes, given teachers' crucial role as primary agents in the learning process. This research is motivated by evidence that low teacher welfare may adversely affect work motivation, productivity, and student learning outcomes, and by the need to formulate evidence-based policy recommendations to improve teacher welfare. The study employed a quantitative approach, administering a questionnaire to 60 teachers across various educational levels in Purworejo Regency. Data were analyzed using simple linear regression to examine the partial effect of teacher welfare on teaching quality and educational quality, and multivariate linear regression to assess the simultaneous effect. Statistical analysis was conducted using IBM SPSS version 25. The results indicate that teacher welfare significantly affects teaching quality and educational quality (p < 0.05). The coefficient of determination indicates that teacher welfare accounts for 54.7% of the variance in teaching quality and 72.7% of the variance in educational quality. These findings imply that improving teacher welfare can substantially enhance instructional performance and overall educational quality and should therefore be a strategic priority in regional educational policy and resource allocation. However, this study is limited by its relatively small sample size and its focus on a single regency, which may restrict the generalizability of the findings to broader contexts